Zero-phonon line as the foundation stone of high-resolution matrix spectroscopy, persistent spectral hole burning, single impurity molecule spectroscopy - Rebane, Karl K. (Chemical physics, 1994)
The purely electronic zero-phonon line (ZPL) - the optical analog of the Mössbauer-γ-resonance line - is a remarkable feature of the low temperature impurity absorption and luminescence spectra of solids. The narrowness and high peak absorption cross section of ZPLs has opened new horizons for high resolution spectroscopy of impurity molecules (centers). The newest and most spectacular achievement is single impurity molecule spectroscopy. Persistent spectral hole burning (PSHB), serving as a tool to control by means of illumination the absorption coefficient, and bound to it, via the Kramers-Kronig relations, the refraction index, turns inhomogeneous broadening of ZPLs into a useful feature and opens a variety of applications including PSHB optical data storage and processing. Space-frequency and space-time domain holographies are developed. The latter comprises the causality relations between events subject to holography and opens new principal possibilities in optics.